Cancer in a polyp of the large intestine – an interdisciplinary decision problem - Przemysław Stefaniak; Hanna Majewska; Dariusz Zadrożny; Janusz Godlewski (Gastroenterology Review)
Large intestine polyps are commonly found during colonoscopies. Pedunculated colon polyps can be totally removed using an endoscopic invasive technique. A problem arises when the pendulated polyp contains cancerous infiltration. The aim of the article was a presentation of the clinical decision process concerned with the presence of cancer invasion tissue within colorectal polyps. Review of literature source and presentation of histological sample photography. A correct interpretation of the pathomorphological protocol is crucial for the therapeutic decision, which should be consistent with the actual recommendations of gastroenterological societies. Local treatment is considered as complete when the adenocarcinoma is well or moderately differentiated without any microinvasion of blood and lymphatic vessels and the resection margin is more than 1 mm from the cancer tissue infiltration. In the contemporary clinical practice patients with a colon polyp require rational clinical decisions, which are based on the actual recommendations.